Effects of endoscopic endonasal sinus surgery on nasal flora in patients with chronic rhinosinusitis with nasal polyps - Ulusoy, Bulent; Muderris, Tuba; Ersoy Callioglu, Elif; Bozdemir, Kazim; Oguzhan, Tolga; Kutluhan, Ahmet; Cibali Acikgoz, Ziya; Hakan Korkmaz, Mehmet (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate the alterations in the nasal flora in patients who underwent endoscopic endonasal surgery for chronic rhinosinusitis with nasal polyps (CRSwNP). Material and Methods: This prospective study included 30 patients diagnosed with CRSwNP who were resistant to medical treatment and recommended for surgery. The nasal cavity was sampled two times, first preoperatively on the day of operation and postoperatively in the 4th week. Patients were divided into two groups according to their culture results, including normal flora bacteria and potential pathogen production. Results: In the preoperative swab samples, 3 (11.1%) patients had no bacterial growth, 16 (59.3%) patients had a normal flora, and potential pathogens were detected in 8 (29.6%) patients. However, postoperatively, 3 (11.1%) patients had no bacterial growth, 13 (48.1%) patients had a normal flora, and potential pathogens were detected in 11 (40.7%) patients during the postoperative period. No significant difference was found between preoperative and postoperative culture results in terms of the number of patients with normal flora, potential pathogens, and no bacterial growth (p=0.676). The most common microorganism in the normal flora group preoperative and postoperative period was coagulase-negative Staphylococcus (77.8%, 51.9%, respectively), and the most common microorganism in the potential pathogen group was Staphylococcus aureus (18.5% and 25.9%, respectively). Comparing preoperative and postoperative culture results according to isolated potential pathogen microorganism types, no statistically significant difference was observed for any microorganism in the potential pathogen group (p>0.05).Conclusion: As a result, no correlation between nasal polyps’ surgery and potential pathogens was detected. Keywords: Chronic rhinosinusitis; culture; nasal polyps; flora; potential pathogens; bacteria; Staphylococcus aureus; coagulase; transnasal endoscopic surgery; pseodomanas.